Paradigma Pemikiran Hubungan Antar Agama di Era Pasca Reformasi sebagai Strategi Resolusi Konflik di Indonesia - Daffa, Muhammad (Integritas Terbuka: Peace and Interfaith Studies, 2025)
Indonesia, as a country with high religious diversity, faces challenges in maintaining interfaith harmony, particularly in the post-Reform era of 1998, which expanded religious freedom while also increasing the risk of religion-based conflicts. This study aims to analyze the paradigm of interfaith relations in the post-Reform period and its contribution to resolving religious conflicts. Using a qualitative approach based on literature studies, this research examines various theories and perspectives of interfaith figures. The key findings indicate four phases in the dynamics of interfaith relations in Indonesia: the interfaith dialogue phase, which led to the emergence of interreligious communities; the advocacy phase, which focused on defending religious freedom rights; the creative campaign phase, which disseminated messages of tolerance through innovative media; and the intersectional phase, which integrates multiple approaches to develop inclusive policies. The academic contribution of this research lies in integrating various paradigms of thought, including neo-modernism, democratic socialism, universalism, liberative modernism, universal humanism, and non-violent conflict resolution, which can be implemented in religious diversity policies in Indonesia. However, this study has limitations in empirical research, and further studies are recommended to assess the effectiveness of these approaches through direct case studies and more specific policy analyses.